Numerical study on the reduction effect of sloshing phenomenon and energy harvesting using a flexible piezoelectric nanogenerator - Muhammad Akbar Asis; Hidemi Mutsuda; Takuji Nakashima; Suandar Baso; Andi Ardianti (Results in Engineering)
Herein, this study explores the use of a flexible piezoelectric device (piezoelectric nanogenerator; PENG) to reduce sloshing motions and harvest electric power from fluid energy, addressing the growing demand for green energy solutions. Through experimental and numerical analyses using Smoothed Particle Hydrodynamics (SPH), the research demonstrates the effectiveness of flexible perforated baffles in reducing sloshing energy, achieving a kinetic energy reduction of 76.42 % for the 3 × 3 configuration and 71.33 % fort the 4 × 4 configuration, while also reducing potential energy by 45.20 % and 33.51 % respectively. Furthermore, the systems enable energy conversion with a maximum power output of 145 mW/m3 for flexible perforated baffles a 3 × 3 configuration and 108.1 mW/m3 for a 4 × 4 configuration. Integrating PENG material into the baffle structure highlights its dual functionality for sloshing suppression and energy harvesting, offering a promising solution for maritime environments. The findings underscore the potential of this innovative approach to enhance energy efficiency and structural stability. Future studies will aim to further optimize flexible baffle designs and explore real-world applications to improved performance and durability.